List of the type specimens of Triatominae (Hemiptera: Heteroptera: Reduviidae) in the Hemimetabola Collection of the Museum für Naturkunde, Berlin - Rodrigues, Juliana Mourão Dos Santos; Moreira, Felipe Ferraz Figueiredo; Deckert, Jürgen; Galvão, Cleber (Zootaxa, 2020)
The Hemimetabola Collection of the Museum für Naturkunde Berlin, Leibniz-Institut für Evolutions- und Biodiversitätsforschung, located in Berlin, Germany, holds types of 22 species of Triatominae (Hemiptera: Heteroptera: Reduviidae) belonging to six genera: Belminus Stål, 1859; Eratyrus Stål, 1859; Meccus Stål, 1859; Panstrongylus Berg, 1879; Rhodnius Stål, 1859; and Triatoma Laporte, 1832. We present a detailed list containing nomenclatural, taxonomic and label data, and photographs of specimens and their labels.